Effect of Diethyl Ether and DIMETHYL Ether With Liquefied Petroleum Gas on Combustion And Emissions Characteristics of Diesel Engine - El-Hagar, Mahmoud Mohamed El-Ghobashy (International Journal of Computer Sciences and Engineering, 2014)
Producing and using renewable fuels for transportation is one approach for sustainable energy future for the world. A renewable fuel contributes lesser global climate change. In this study the effect of using liquefied petroleum gas (LPG) as a primary fuel with two different ignition enhancers diethyl ether (DEE) and dimethyl ether (DME) on performance, combustion and emissions characteristics of a single cylinder, four-stroke, water-cooled naturally aspirated DI diesel engine was carried out. LPG has a simpler hydrocarbon structure than conventional fuels. DEE and DME are recently reported as a renewable fuel and to be a low-emission high-quality diesel fuel replacement. A single cylinder, four-stroke, water-cooled naturally aspirated DI diesel engine having rated output of 3.7kW at 1500 rpm was used for the experiments. Measurements were made to study the performance, combustion and emissions characteristics and to compare between these two ignition enhancers and conventional diesel fuel. From the results, it is observed that using LPG/DEE was better than LPG/DME on performance, combustion and emissions characteristics of diesel engine and both were better than conventional diesel fuel, especially in a reduction of NO, smoke and particulate emissions. The brake thermal efficiency for both LPG/DEE and LPG/DME lower at full load with a reduction of NO emission than the diesel operation. The maximum reduction in smoke and particulate emissions is observed at high loads, when compared to that of diesel operation; however an increase in CO and HC emissions was observed.